Preliminary Study of Stress Distribution on Modified Femoral Component of Knee Implant at Maximum Flexion Angle - Fua-Nizan, R. (Springer, 2020)
Human knee is an important joint in human body that allows leg movement. However, the cartilage can lose their shape and damage the bone due to illness. Total knee replacement is a medical procedure that replaced the bones with knee implant. However, difference in anatomy between Caucasian and Asian has caused some concern in the fit of the knee implant and most knee implants in the market were not designed for greater flexion ability of Asian population. Hence, a customized femoral component for high flexion application was designed and analysed utilizing DICOM image of MRI scanned knee. Stress distribution analysis was conducted on the femoral component to study the effect of high flexion on the modified femoral component. Preliminary results showed that the stress distribution was relatively higher at smaller contact area. The result concluded that there was a possibility of failure on the modified femoral component due to high stress concentration. Â© 2020, Springer Nature Singapore Pte Ltd.